Molecular characterization of four giant gourami strains from Java and Sumatra - AGUS NURYANTO; GINA AMALIA; DAINTY KHAIRANI; HENDRO PRAMONO; DIAN BHAGAWATI (Biodiversitas Journal of Biological Diversity, 2018)
Nuryanto A, Amalia G, Khairani D, Pramono H, Bhagawati D. 2018. Molecular characterization of four giant gourami strains from Java and Sumatra. Biodiversitas 19: 578-584. Giant gourami (Osprhonemus goramy) are widely distibuted across Indonesia, such Java, Sumatra, and Kalimatan which lead to the emerge of various gourami strains due to morphological differences. However, no scientific data about the relationship between morphological and genetic differences among strains. This research aimed to obtain information on molecular characteristics of four giant gourami strains from Java and Sumatra based on partial sequences of cytochrome c oxidase 1 gene. This information is vital to strengthen their taxonomic status. Caudal fin clips were sampled from each strain. Nucleotide sequencing was performed using bigdye terminator tehcnique. Pairwise Fst comparison was carried out using arlequin software, whereas sequences of divergence analysis was performed in DnaSP software. Homology of the sequences were checked with previous published data available in Boldsystem data base. Homology test resulted in 98.79 to 100% similarity to the previous published sequences. This means that all strains belonged to single species, i.e. Osphronemus goramy. This placement was supported by low-level of genetic divergences among strains. Although they have low-level genetic divergences, this value is suitable to separate each strain clearly as indicated by pairwise Fst comparison analysis and AMOVA, which showed differences among strains. However, phylogenetic tree shows that all stains formed a monopyletic group with boostratp value of 100. Phylogenetic analysis supports the placement of all strains into a single species that is O. guramy. Those morphological differences are also reflected in their genetic character, except for Tambago and Oranye strains.